Select document: A settlement between the canons of St Thomas's Abbey, Dublin, and Walter de Lacy concerning the church of Ardmulchan granted to the canons by Theobald Walter. Issue 165 (May 2020) - Flanagan, Marie Therese
Abstract: A hitherto unpublished text of a negotiated settlement between Walter de Lacy, lord of Meath (d. 1241), and the canons of St Thomas's Abbey, Dublin, relating to the church of Ardmulchan in County Meath sheds new light both on the career of Theobald Walter I (d. 1205), ancestor of the Butler earls of Ormond, and on the dealings of John, son of King Henry II of England, with his Irish lordship during the period 1185–99 for which sources are scarce. It indicates that not only in Leinster, but also in Meath, John encroached on the seigneurial rights of Anglo-Norman landholders.